Free vascularized osteoseptocutaneous fibular flap for radius shaft nonunion: The final solution when the iliac crest autograft fails. A case report. (December 2018) - Vicenti, Giovanni; Maruccia, Michele; Carrozzo, Massimiliano; Elia, Rossella; Giudice, Giuseppe; Moretti, Biagio
Abstract: Treatment of forearm nonunion associated with bone defects can be challenging. Restoring the correct length and rotation are two main principles for the management of these patients. Herein, we describe a patient with isolated radius nonunion already treated with an iliac crest autograft with no success. A free vascularized osteoseptocutaneous fibular autogenous graft was harvested as the final solution to managed long bone defect after previous multiple surgeries. At the 1- year follow-up, the patient gained full range of motion and was functioning well.